Dual form of malnutrition in the Gaza Strip - Palestine Territories : prevalence, associated determinants and women's knowledge and perception of nutrition practices - Kishawi, Rima R.R.El (2015)

(untitled)
In the Gaza Strip, obesity increased among adults and underweight among preschool children were prevalent. The coexistence of these findings led to the hypothesis that obesity and underweight can cluster within a household to emerge dual form of malnutrition in the same household. The main purpose of this study was to understand the profiles of malnutrition among mothers and children aged 2-5 years then in so doing, to address the dual form of malnutrition (overweight mother/underweight child) in the same household in the Gaza Strip. More specifically, to investigate the associated factors with child underweight, maternal overweight pairs, and explore the mothers’ nutrition perception and knowledge. This study used quantitative and qualitative mixed methods design. Phase I, cross-sectional study represents a quantitative data set to assess dual form of malnutrition and its associated risk factors among mothers’ childbearing aged 18–50 years, and children aged 2-5 years. Some 357 households from three different geographical locations in the Gaza Strip, namely, El Remal urban area, Jabalia refugee camp, and Al Qarara rural area participated in this study. Data were collected using structured questionnaire for face to face interviews. Height and weight for mothers and children were measured, International Physical Activity Questionnaire (IPAQ) was used to measure the physical activity pattern of mothers, 24-Hour recall was used to assess nutrients intake for mother-childpairs, and all 357 children and mothers voluntarily provided blood samples for biochemical tests. In phase II, focus groups discussions were performed to explore mothers’ nutrition knowledge and perception. Twenty four of surveyed overweight or obese mothers were recruited from the three locations in the Gaza Strip. Results from phase I study showed that, about 59.7% of children aged 2-5 years were anemic, 24.4% were underweight Z-score<-1.0, whereas more than half of mothers 64.1% were overweight or obese. The prevalence of dual form of malnutrition was 15.7%. Child birth order had significant association with dual form of malnutrition (ORadj, 1.50, 95% CL (1.22, 1.82); p=<0.001). Household with dual form of malnutrition increased as father’s educational decreased (medium or low level) (ORadj, 3.19, 95% CL (1.07, 9.5); p=0.036), or (ORadj, 3.40, 95% CL (1.12, 10.37); p=0.031), respectively. In addition, child with poor appetite was more likely to be underweight and also significantly associated with dual form of malnutrition (ORadj, 6.9, 95% CL (2.35, 20.24); p<0.001). Dual form of malnutrition increased among mothers with high nutrition knowledge level (ORadj, 1.23, 95% CL (1.0, 1.52); p=0.048). Dual form of malnutrition decreased in households with low monthly income (ORadj, 0.28, 95% CL (0.09, 0.88); p=0.030).With regard to nutrient intake, mother’s fat intake contributing to obesity was associated with the dual form of malnutrition (ORadj, 1.01, 95% CL (1.0, 1.02); p=0.016). In part II, results supported the results of part I, that Palestinian mothers had good nutrition knowledge, but poor nutrition attitude and practice. Knowledge didn’t convey to healthy practice, therefore, nutrition knowledge and the negative attitudes of mothers contributed in increasing malnutrition among individuals at household level. Cultural factors and mothers’ poor perception have a powerful influence on feeding practices and eating patterns. This research broadens the understanding of the correlating factors of familial coexistence of underweightchildren and overweight mothers. In this study, child undernutrition still exists, with increasing levels of maternal obesity as well as the dual burden of malnutrition. Nutrition intervention programs must recognise the coexistence of both extremes of malnutrition at household level, and incorporate this into their targeting strategies in order to manage the dual burden of malnutrition effectively. These new insights suggest programs specifically designed for resource-poor settings to promote healthy eating habits and regular physical activity that prevent both child undernutrition and the adult obesity.